Drivers and Reversibility of Abrupt Ocean State Transitions in the Amundsen Sea, Antarctica. Issue 1 (30th December 2022) - Caillet, Justine; Jourdain, Nicolas C.; Mathiot, Pierre; Hellmer, Hartmut H.; Mouginot, Jérémie
Abstract: Ocean warming around Antarctica has the potential to trigger marine ice‐sheet instabilities. It has been suggested that abrupt and irreversible cold‐to‐warm ocean tipping points may exist, with possible domino effect from ocean to ice‐sheet tipping points. A 1/4° ocean model configuration of the Amundsen Sea sector is used to investigate the existence of ocean tipping points, their drivers, and their potential impact on ice‐shelf basal melting. We apply idealized atmospheric perturbations of either heat, freshwater, or momentum fluxes, and we characterize the key physical processes at play in warm‐to‐cold and cold‐to‐warm climate transitions. Relatively weak perturbations of any of these fluxes are able to switch the Amundsen Sea to an intermittent or permanent cold state, that is, with ocean temperatures close to the surface freezing point and very low ice‐shelf melt rate. The transitions are reversible, that is, canceling the atmospheric perturbation brings the ocean system back to its unperturbed state within a few decades. All the transitions are primarily driven by changes in surface buoyancy fluxes resulting from the freshwater flux perturbation or from modified net sea‐ice production due to either heat flux or sea‐ice advection anomalies. These changes affect the vertical ocean stratification over the continental shelf and thereby the eastward undercurrent at the shelf break, which both impact ice‐shelf melting. As sea‐ice induced deep convection is already quite limited in present‐day conditions, surface buoyancy gain in a warmer climate has relatively little effect on deep ocean properties compared to colder climate conditions. Plain Language Summary: The West Antarctic Ice Sheet is under the threat of a partial collapse, which would induce rapid global sea level rise. This threat is partly related to the thinning of floating ice shelves, and the consequent retreat of the grounding line, which is a self‐sustained ice dynamics process. It is triggered by increased basal melting of the ice shelves, which results from enhanced flow of relatively warm waters onto the continental shelf. It has been suggested that self‐sustained ocean processes may lead to abrupt changes in the flow of warm water into ice‐shelf cavities, which could facilitate the tipping to a marine ice‐sheet instability. Here, we analyze whether such abrupt ocean changes can occur under cold‐to‐warm or warm‐to‐cold transitions in the Amundsen Sea, West Antarctica. We use a regional ocean model with a set of idealized local atmospheric perturbations to characterize the thresholds and reversibility of ocean abrupt changes.We find that the currently warm Amundsen Sea could switch intermittently or permanently to a cold state for relatively weak atmospheric perturbations and could be slightly warmer in the future. All transitions are reversible. The main mechanism involved on decadal scale is related to a change in the surface buoyancy fluxes. Key Points: The currently warm ice‐shelf cavities of the Amundsen sector could become or have been cold for slightly colder climatic conditions The transitions are reversible: canceling the atmospheric perturbation brings the ocean back to its unperturbed state within a few decades All the transitions are primarily driven, at multi‐decadal scale, by changes in surface buoyancy fluxes over the continental shelf